Environmental Law, Populism, and Welfare State: Discourse on Environmental Law in the 21st Century - Ladlul Muksinin; Aminah Aminah (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2021)
In the 21st century, the problems of environmental law in various parts of the world are getting more and more alarming. The research results by Elizabeth Fisher (2019) and Sanja Bogojevic (2019) indicate that several environmental law policies have been controlled by populism, as happened in several countries in Europe. Populism is transformed into a movement of people's will which certainly has an impact on the enforcement of environmental laws by various countries around the world. For this reason, this paper intends to discuss the law and to find the definition and influence of populism in protecting environmental laws in the welfare state. The aim was to determine a picture of populism and its influence on the development of environmental law. The result is that populism as an idea or ideology also means a discursive style, and it can also be interpreted as a form of political mobilization. The rise of populism threatens the development of environmental law. Populist attitudes lead to climate skepticism on environmental protection. Environmental protection may provide idealized targets for populists by framing this issue area as an elite project. Individuals who display highly populist attitudes perceive a lack of representation in these issue areas and, therefore, because of the problem of anti-elitism, reject climate and environmental policies. In other words, elite resistance tends to be associated with climate skepticism and lower support for environmental protection.